Inclusions and Exclusions in Work-Family Policy: The Public Values and Moral Code Embedded in the Family and Medical Leave Act - Bornstein, Lisa (Columbia Journal of Gender and Law, 2000)
The United States has done little to help working families. We lack any comprehensive national family policy. We were among the last industrialized nations to pass parental leave legislation.2 Historically, governmental action on work and family issues, constrained by values of privacy, autonomy, self-sufficiency, and minimal government interference,3 has been limited to piecemeal responses to headline grabbing outrages. Recently, however, with the demographic changes in American families, the increasing participation of women in the workforce, the aging of the population, and the evolution of the employer-employee relationship, the government has been forced to confront the reality of the work-family dilemmas faced by many Americans. Yet this government involvement has been profoundly shaped by the “reality that [c]ultural assumptions are at the root of government policies.”